Study of the Interaction Between S-Ovalbumin and Resveratrol with Spectroscopic Techniques - Huang, Qun; Geng, Fang; Ma, Meihu; Jin, Yongguo; Fang, Jun; Sun, Shuguo (Asian Journal of Chemistry, 2013)
The interaction between resveratrol and S-ovalbumin was studied by using fluorescence quenching spectra, synchronous fluorescence spectra and ultraviolet spectra. The results indicated that resveratrol has the ability to quench the intrinsic fluorescence of S-ovalbumin because of a complex formed and the quenching was a static event. Furthermore, the quenching efficiency decreased with the rise in temperature. The binding constants were 3.49 × 106 and 4.42 × 104 L mol-1 and binding site were 1.39 and 1.04 at 303 and 318 K, respectively. Thermodynamic analysis results suggested that both hydrogen bonds and van der Waals forces played a key role in the interaction. According to the Förster theory of non-radiation energy transfer, the distance between S-ovalbumin and resveratrol and the energy transfer efficiency were calculated as 3.94 nm and 0.11, respectively. The conformational alteration of S-ovalbumin in the presence of resveratrol was also verified by means of synchronous fluorescence spectra and UV-visible absorption spectra.